UPAYA PENINGKATAN PENGETAHUAN MENGENAI KESEHATAN REPRODUKSI REMAJA PADA PELAJAR SMP NEGERI 1 BATANG KAPAS KABUPATEN PESISIR SELATAN - Refa Rahmaddiansyah; Sukarsi Rusti; Fettriwanti Fettriwanti (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
Health is one of the most important sectors in realizing sustainable development goals in the world. The welfare of young people or teenagers and cross-sector collaboration are the main factors in future change. The many problems that concern teenagers, such as early marriage, risky pregnancies and sexually transmitted diseases, are challenges in themselves, so various efforts are made, especially in promoting education regarding reproductive issues for teenagers. This educational activity was carried out on students at SMPN 1 Batang Kapas, Pesisir Selatan Regency who were categorized as teenagers. Activities include education about reproductive health and evaluation of the level of knowledge through pretest and posttest. The activity method carried out is in the form of delivering material using the lecture/demonstration method. The activity aims to promote teenagers' understanding of reproductive health and keep them away from negative associations. The results of the activity showed that there were no significant differences between the pretest and posttest because respondents had received information from various sources, both print and digital. The average knowledge of respondents regarding reproductive health is good (74%). The role of parents and peers is the most important thing in shaping a teenager's personality and mindset to avoid bad behavior. It was concluded that the program was running well and it was hoped that it would be useful for students to maintain their reproductive health. It is recommended to provide counseling using more interactive and innovative methods to increase students' interest in the material presented.